Molecular interaction between prion protein and GFAP both in native and recombinant forms in vitro - Chen-Fang Dong; Xiao-Fan Wang; Xin Wang; Song Shi; Gui-Rong Wang; Bing Shan; Run An; Xiao-Li Li; Bao-Yun Zhang; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2008)

Isolation and characterization of microsatellite markers for the endangered Taxus yunnanensis - Ying-Chun Miao; Jian-Rong Su; Zhi-Jun Zhang; Hui Li; Jing Luo; Ya-Ping Zhang (Conservation Genetics, 2008)

Systematic biotic responses to palaeoenvironmental change in the Late Pleistocene southern South China Sea: a preliminary study - Muhong Chen; Qianyu Li; Lanlan Zhang; Fan Zheng; Jun Lu; Rong Xiang; Lili Zhang; Wen Yan; Zhong Chen; Shangbin Xiao (Journal of Quaternary Science, 2008)
Oxygen and carbon isotopes from the planktonic foraminifer Globigerinoides sacculifer , trace element contents, calcium carbonate, biogenic silica, grain size, and abundances of diatoms, radiolarians and foraminifera in a deep‐sea core from the southwestern South China Sea were analysed to investigate the response of various marine ecological communities to environmental changes over the last 200 ka. The synthesised results show that the quality of the palaeoecological environment for biological growth is primarily affected by nutrient supply and terrigenous disturbance. Ba and P are important nutrient elements for the growth of diatoms, radiolarians and planktonic foraminifera. Together with dissolved silica and calcium carbonate in sea water, these elements may control microbiotic development. However, variations in Fe content appear to affect diatom and radiolarian abundance. Optimal biotic growth occurs when nutrients are abundant and when there is minimal terrigenous disturbance. Biotic growth decreases when sea water is highly oligotrophic and terrigenous input is high. Maximum biological growth occurred in the mid Holocene, but deteriorated soon afterwards owing to increased terrigenous input, causing a decrease of biological abundance and productivity in the late Holocene. The results also indicate how the Toba volcanic eruption ca. 74 ka ago contributed to changing the ecological environment in the southern South China Sea. Copyright © 2008 John Wiley & Sons, Ltd.

Cloning and characterization of phosphorus starvation inducible Brassica napus PURPLE ACID PHOSPHATASE 12 gene family, and imprinting of a recently evolved MITE-minisatellite twin structure - Kun Lu; You-Rong Chai; Kai Zhang; Rui Wang; Li Chen; Bo Lei; Jun Lu; Xin-Fu Xu; Jia-Na Li (Theoretical and Applied Genetics, 2008)

Fluorescent co-localization of PTS1 and PTS2 and its application in analysis of the gene function and the peroxisomal dynamic in Magnaporthe oryzae - Jiao-yu Wang; Xiao-yan Wu; Zhen Zhang; Xin-fa Du; Rong-yao Chai; Xiao-hong Liu; Xue-qin Mao; Hai-ping Qiu; Yan-li Wang; Fu-cheng Lin; Guo-chang Sun (Journal of Zhejiang University-SCIENCE B, 2008)

Microbial composition and diversity of an upland red soil under long-term fertilization treatments as revealed by culture-dependent and culture-independent approaches - Ji-Zheng He; Yong Zheng; Cheng-Rong Chen; Yuan-Qiu He; Li-Mei Zhang (Journal of Soils and Sediments, 2008)

CYP3A4*1G polymorphism is associated with lipid-lowering efficacy of atorvastatin but not of simvastatin - Yuan Gao; Li-rong Zhang; Qiang Fu (European Journal of Clinical Pharmacology, 2008)

Cadmium Accumulation in the Edible Parts of Different Cultivars of Radish, Raphanus sativus L., and Carrot, Daucus carota var. sativa, Grown in a Cd-contaminated Soil - Rui-Lun Zheng; Hua-Fen Li; Rong-Feng Jiang; Fu-Suo Zhang (Bulletin of Environmental Contamination and Toxicology, 2008)

Nematicidal coumarins from Heracleum candicans Wall. - Xing-Biao Wang¶; Guo-Hong Li¶; Lei Li; Li-Jun Zheng; Rong Huang; Ke-Qin Zhang (Natural Product Research, 2008)

Proteiomic patterns for endometrial cancer using SELDI-TOF-MS - Li-rong Zhu; Wen-ying Zhang; Li Yu; Yan-hua Zheng; Jun Hu; Qin-ping LIAO (Journal of Zhejiang University-SCIENCE B, 2008)

Reduced expression of GSTM2 and increased oxidative stress in spontaneously hypertensive rat - Si-Gui Zhou; Ping Wang; Rong-Biao Pi; Jie Gao; Jia-Jia Fu; Jian Fang; Jia Qin; Hui-Jie Zhang; Rui-Fang Li; Shao-Rui Chen; Fu-Tian Tang; Pei-Qing Liu (Molecular and Cellular Biochemistry, 2008)

Sensing Escherichia coli O157:H7 via frequency shift through a self-assembled monolayer based QCM immunosensor - Li-jiang Wang; Chun-sheng Wu; Zhao-ying Hu; Yuan-fan Zhang; Rong Li; Ping Wang (Journal of Zhejiang University-SCIENCE B, 2008)

Persistence and dissipation of synthetic pyrethroid pesticides in red soils from the Yangtze River Delta area - Xiao-zhi Gu; Gang-ya Zhang; Li Chen; Rong-ling Dai; Yuan-chun Yu (Environmental Geochemistry and Health, 2008)

Isolation of a new repetitive DNA sequence from Secale africanum enables targeting of Secale chromatin in wheat background - Cheng Liu; Zu-Jun Yang; Guang-Rong Li; Zi-Xian Zeng; Yong Zhang; Jian-Ping Zhou; Zhao-Hui Liu; Zheng-Long Ren (Euphytica, 2008)